PENGARUH KOMUNIKASI PEMASARAN WISATA KUSUMA TIRTA MINAPOLITAN TERHADAP PENINGKATAN KUNJUNGAN WISATA BAHARI DI KABUPATEN SIDOARJO - Dyah Ary Setya Ningrum (Kanal: Jurnal Ilmu Komunikasi, 2015)
The purpose of this research was to determine how marketing communications affect to the increase visits in the Marine Tourism Minapolitan Kusuma Tirta Sidoarjo. The method used quantitative explanative. This study population was an overall visitor Tirta Kusuma Minapolitan consisted of 100 people. The sampling technique in this research used Taro Yamane. This study used regression analysis with simple regression methods. Primary data collection technique used Likert Scale. The results of this study can be concluded that marketing communications activities have a significant impact on tourist visits to the Tirta Kusuma Minapolitan of value R 0.572 with a percentage of 32.7%.